2018
DOI: 10.18520/cs/v114/i05/1036-1045
|View full text |Cite
|
Sign up to set email alerts
|

Regional Scale Analysis of Climate Extremes in an SRM Geoengineering Simulation, Part 2:Temperature Extremes

Abstract: In this study, we examine the statistics of temperature extremes in a model simulation of solar radiation management (SRM) geoengineering. We consider both intensity and frequency-based extreme indices for temperature. The analysis is performed over both large-scale domains as well as regional scales (22 Giorgi land regions). We find that temperature extremes are substantially reduced in geoengineering simulation: the magnitude of change is much smaller than that occur in a simulation with elevated atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…A few studies under the Geoengineering Model Intercomparison Project (Kravitz et al, 2011) have analyzed the climate effects that result from simulating SRM in specific ways, including the effects on mean climate, extreme events, and hydrology (Curry et al, 2014;Kravitz et al, 2013;Muthyala et al, 2018aMuthyala et al, , 2018bTilmes et al, 2013). While SRM could potentially reduce global surface temperature it could also reduce global precipitation (Bala et al, 2008;Robock et al, 2008;Tilmes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies under the Geoengineering Model Intercomparison Project (Kravitz et al, 2011) have analyzed the climate effects that result from simulating SRM in specific ways, including the effects on mean climate, extreme events, and hydrology (Curry et al, 2014;Kravitz et al, 2013;Muthyala et al, 2018aMuthyala et al, , 2018bTilmes et al, 2013). While SRM could potentially reduce global surface temperature it could also reduce global precipitation (Bala et al, 2008;Robock et al, 2008;Tilmes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies examined the impact of SRM on climate extremes. For example, under the framework of the Geoengineering Model Intercomparison Project (GeoMIP) (Kravitz et al, 2013;Visioni & Kravitz et al, 2023), a few studies have explored changes in climate extremes in response to different SRM methods including solar dimming (Curry et al, 2014;Ji et al, 2018;Muthyala et al, 2018aMuthyala et al, , 2018b, SAI (Aswathy et al, 2015;Ji et al, 2018;Wei et al, 2018), and marine cloud brightening (Aswathy et al, 2015;Kim and Shin, 2020). These results showed that these SRM methods can mitigate the changes in climate extremes induced by GHG emissions with various degrees, but different SRM methods would lead to heterogeneous impacts on regional climate extreme events.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when cirrus cloud thinning (CCT) is used to offset CO 2 ‐induced global warming, it usually increases global mean precipitation relative to climate conditions before CO 2 increased (Kristjánsson et al, 2015; Helene Muri et al, 2018, Duan et al, 2018). The induced cooling by radiation modification approaches would also prevent melting of sea ice and snow, and reduce extreme events that would occur otherwise under higher CO 2 levels (Curry et al, 2014; Irvine et al, 2019; Ji et al, 2018; Kravitz, Caldeira, et al, 2013; Moore et al, 2014; Muthyala et al, 2018a, 2018b). To determine the robustness of simulated climate responses to different radiation modification approaches, Geoengineering Model Intercomparison Project (GeoMIP) has been conducted, in which over a dozen climate models simulate the climate responses to radiation modification under the same experimental protocol (Kravitz et al, 2011, 2015).…”
Section: Introductionmentioning
confidence: 99%